THEORETICAL AND METHODOLOGICAL ASPECTS OF INDIVIDUAL ECONOMIC SECURITY - Bobir O.Tursunov (Scholar Express Journals, 2024)
In this article has been provided a methodological analysis of the main approaches to determining the economic security of an individual. The author examines the prism of the structure of the individual’s economic security through national, state, public interests, economic independence and through stability or sustainability (national economy, economic development, socioeconomic system
Keywords: Economic Security; Economic Security Of The Individual; Economic Policy